Catalytic microwave-assisted pyrolysis of plastic waste over NiO and HY for gasoline-range hydrocarbons production. (15th September 2019) - Ding, Kuan; Liu, Shasha; Huang, Yong; Liu, Shiyu; Zhou, Nan; Peng, Peng; Wang, Yunpu; Chen, Paul; Ruan, Roger
Graphical abstract: Highlights: Catalytic pyrolysis of LDPE was performed in a microwave reactor. NiO and HY zeolite were used as in-situ and ex-situ catalysts, respectively. 56.5 wt% of oil and 93.8% of gasoline fraction were obtained over HY catalysis. Adding NiO improved the octane number of the oil with minor effects on its yield. The pyrolysis mechanism of LDPE over NiO and HY was proposed. Abstract: Recovering fuels or chemicals from plastic waste via pyrolysis is an innovative and promising route for both energy saving and refuse elimination. In this study, catalytic microwave-assisted pyrolysis of low-density polyethylene (LDPE) was performed to simultaneously improve yield and quality of gasoline-range products. NiO and HY zeolite were respectively used as in-situ and ex-situ catalysts in a two-stage pyrolysis-catalysis system. The results showed that the optimum pyrolysis and catalysis temperatures were 500 °C and 450 °C, respectively, with 56.53 wt% oil product and 93.80% gasoline-range fraction achieved. The content of high-octane-number compounds, primarily aromatics and isomerized aliphatics, increased from 23.5% to 80.4% as HY to LDPE ratio rose from 0 to 1:5. The optimized balance between oil yield and oil quality was obtained at the HY to LDPE ratio of 1:10. The presence of NiO during co-catalysis slightly decreased the oil yield by 5.3–8.5 wt%. Meanwhile, the production of aromatics was promoted obviously while the yield of normal aliphatics was inhibited, which were both favorable to improve the octane number of the oil product. The improved performance of co-catalysis could be related to the suitable hydrogen abstraction ability of NiO, which produced enormous alkenes. Subsequently, cycloalkenes and aromatics were synthesized through Diels-Alder reactions over the catalysis of HY. This co-catalysis approach in the microwave reactor provides a potentially profitable way to convert plastic waste into high-quality and high-yield gasoline fuels.